ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP PELAYANAN DABU – DABU LEMONG BOULEVARD KARANGRIA - Herlina Anggie Tangkere; Joachim Noch Karel Dumais; Tommy Fredy Lolowang (Sam Ratulangi University, 2020)
The purpose of this study was to analyze the level of customer satisfaction with the services provided by the